Exploring Lexical Inaccuracy in Arabic-English Translation Implications and Remedies - Alenazi, Yasir (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book presents a case study on lexical error analysis in the translation products of Arab English majors at the university level with important implications for Arabic-speaking countries. It provides detailed analyses and explanations of the main lexical areas that cause specific difficulties for these students, while also identifying their potential sources. The respective chapters discuss several areas related to the context of the research, the field of SLA, error analysis, language transfer, error taxonomies, language learning, language teaching, and translation training. The analyses and findings presented here contribute to the linguistic field by developing a comprehensive list of lexical error categories based on form, content, and origin of influence regarding translation products. In addition, the book sheds light on the pedagogical aspects contributing to the enhancement of ESL/EFL teaching in the Arab context as well as other contexts where English is taught as a foreign language. The book will help educators and curriculum writers in designing materials, and language researchers as a groundwork for their studies of L2 learners' written products.
Introduction -- Background -- Statement of the Problem -- Goals of the Study -- Questions of the Study -- Significance of the Study -- Organisation of the book -- Literature Review -- The Significance of Lexis -- The Teaching of Lexis -- Lexical Errors: Approaches to Examine Language Errors -- Sources of Language Errors -- A Brief Overview of Arabic Lexis -- EA Studies on L2 Learners' Lexical Errors -- Summary of the Identified Gaps in the Literature -- Research Design and Methodology -- Introduction -- Theoretical Framework: Error Analysis -- Conceptual Framework: Lexical Error Taxonomy -- Research Design -- Summary and Conclusion -- Formal Lexical Error Analysis -- Introduction -- Quantitative Analysis and Description of Formal Lexical Errors -- Discussion and Explanation of Formal Lexical Errors -- Conclusion -- Semantic Lexical Error Analysis -- Introduction -- Quantitative Analysis and Description of Semantic Lexical Errors -- Discussion and Explanation of Semantic Lexical Errors -- Conclusion -- Implications for Language Learning, Translation, and Language Teaching -- Introduction -- Implications for Language Learning -- Implications for the Translation Studies -- Implications for Language Teaching -- A Summary of the Analysis Impacts on Language Learning, Translation Studies and Language Teaching -- Conclusion -- Summary, Conclusion, and Recommendations -- Introduction -- Overview of the Research Project -- Summary of the Major Findings -- Contributions of the Study -- Recommendations for Teaching Vocabulary and Alleviating the Related Language Errors -- Limitations of the Study -- Suggestions for Future Research.
Keywords: Translating and interpreting; Lexicology; Teaching; Language acquisition; Language and languages-Study and teaching; Language Translation; Lexicolopgy / Vocabulary; Pedagogy; Language Acquisition and Development; Language Education